(untitled) (International journal of medical sciences, 2026)
Background: The success of dental implantation is largely determined by the quality of osseointegration and the preservation of marginal bone levels. While the traditional protocol involves a delayed loading period to ensure stress-free healing, recent trends suggest that early functional loading may stimulate bone remodeling and accelerate healing. Objective: The aim of this study is to evaluate the effectiveness of fixed prosthetics on implants with early functional loading based on clinical and functional studies, specifically focusing on bone tissue dynamics and microcirculation. Methods: The study involved 90 patients aged 25 to 61 years with partial edentulism. Patients were divided into three groups: Group 1 received two-stage implants with delayed loading; Group 2 received implants with early functional loading (prosthetics after 1 month); and Group 3 received traditional bridge prostheses on natural teeth. Assessment methods included 3D radiography (CBCT) to monitor bone density, Laser Doppler Flowmetry (LDF) to evaluate microcirculatory bed hemodynamics, and resonance frequency analysis to measure implant stability. Monitoring was conducted at 1, 3, 6, 9, and 12 months. Results: The study revealed that controlled early functional loading provides a physiological stimulus to the peri-implant bone tissue, preventing atrophy associated with disuse. LDF data showed a faster recovery of microcirculation in the early loading group compared to the delayed group. 3D radiographic analysis demonstrated stable bone levels and increased mineralization density in the functional loading group over the 12-month period. Conclusion: Early functional loading of dental implants, when applied with proper indication, accelerates the rehabilitation process and ensures high stability of the implant through the stimulation of osteogenesis and angiogenesis.